Efeito de cicatrizadores revestidos com Estrôncio sobre parâmetros clínicos peri-implantares. Estudo clínico controlado randomizado em modelo de boca dividida - Goulart, João Vítor (2023)
The aim of this study was to evaluate the effect of strontium-coated (Sr) healing abutments on peri-implant clinical parameters through a controlled, randomized, split-mouth clinical trial. 24 partially edentulous patients in the maxilla or mandible were selected to receive in the same dental arch (2 implants in the maxilla or 2 implants in the mandible) two implants of the same model, macro and microgeometry (conical implant with compacting threads, morse taper connection and hydrophilic surface) in which were randomly installed 1) conventional polished titanium healing abutment or 2) Sr-coated healing abutment. The visible plaque index (VPI), depth on probing (DP) and bleeding on probing (BP) were analyzed at 1, 2 and 3 months after the surgical procedure. The surface area covered by biofilm adhered on the healing caps was analyzed and measured using scanning electron microscopy (SEM). The healing caps’s surface’s chemical composition was also evaluated after 3 months of permanence in the oral cavity by energy dispersive X-ray spectroscopy (EDS). As result, no relevant clinical difference was observed in DP and VPI, however, the strontium-coated healing caps had lower BP in the peri-implant mucosa, despite the greater coverage area of the Sr-coated healing abutment covered by biofilm. Sr-coated healing abutments showed a greater presence of carbon adhered to their surface, as well as maintaining the presence of Sr after 3 months of permanence in the oral cavity. Sr-coated healing abutments reduced inflammation during the implant’s osseointegration period but retained a greater amount of biofilm adhered to their surface.